F^-1(x)= (x+7)/2
it's the inverse so adding is subtracting and multiplication is divison
A = 54 because alternate interior angles
b = 72 because 54+54=108 and 180-108=72
c = 108 because b and c are supplemental angles
d = 72 because b and d are corresponding angles
e = 162 because 72+90=162 and definition of a straight line
f = 18 because definition of a straight line
g = 81 because definition of an isosceles triangle
h = 49.5 because vertical angles and definition of an isosceles triangle
i = 130.5 because definition of a straight line
j = 31.5 because 49.5-18=31.5
k = 99 because corresponding angles
bcegk = 540
First we have to rewrite this function.Instead of :^3 sqrt (...) we can write : (...)^(1/3).
f ( x ) = ( 27 x - 81 ) ^(1/3) - 5 = ( 27 * ( x - 3 ) ) ^(1/3) - 5 = = 3 * ( x - 3 )^(1/3) - 5 And this makes it easy to graph a translation.The parent function is y = x^(1/3). The zero of this function is ( 0, 0 ).
Then it will be stretched vertically by a factor of 2 and translated: 3 units right and 5 units down.
It has to be the second one and it’s part of that answer or maybe it’s the third one